A size-shrinkable matrix metallopeptidase-2-sensitive delivery nanosystem improves the penetration of human programmed death-ligand 1 siRNA into lung-tumor spheroids - Jiaolin Wen; Neng Qiu; Zejiang Zhu; Peng Bai; Mengshi Hu; Wenyan Qi; Yan Liu; Ailin Wei; Lijuan Chen (Taylor & Francis Group, 2021)
Given the maturation of small-interfering RNA (siRNA) techniques with nanotechnology, and because overexpression of human programmed death-ligand 1 (PD-L1) is crucial for T cell inactivation and immunosuppression of the tumor microenvironment, application of siRNA-PD-L1 has demonstrated positive progress in preclinical studies; however, the limited penetration of this compound into solid tumors remains a challenge. To decrease PD-L1 expression and increase the penetration efficacy of solid tumors, we synthesized a novel tumor-microenvironment-sensitive delivery polymer by conjugating hyaluronic acid (HA) to polyethyleneimine (PEI), with a matrix metalloproteinase-2 (MMP-2)-sensitive peptide acting as the linker (HA-P-PEI), for use in delivery of PD-L1-siRNA. Concurrent synthesis of a linker-less HA-PEI compound allowed confirmation that negatively charged siRNA can be complexed onto the positively charged HA-PEI and HA-P-PEI compounds to form nanoparticles with the same particle size and uniform distribution with serum stability. We found that the size of the HA-P-PEI/siRNA nanoparticles decreased to <10 nm upon addition of MMP-2, and that H1975 cells overexpressing CD44, PD-L1, and MMP-2 aided confirmation of the delivery efficacy of the HA-P-PEI/siRNA nanocomplexes. Additionally, the use of HA-P-PEI caused less cytotoxicity than PEI alone, demonstrating its high cellular uptake. Moreover, pretreatment with MMP-2 increased nanocomplex tumor permeability, and western blot showed that HA-P-PEI/PD-L1-siRNA efficiently downregulated the PD-L1 expression in H1975 cells. These results demonstrated a novel approach for siRNA delivery and tumor penetration for future clinical applications in cancer treatment.